A INTELIGÊNCIA ARTIFICIAL E O PANORAMA CONTEMPORÂNEO DA FILOSOFIA DA MENTE EM UM ESTUDO INTRODUTÓRIO PARA A FORMA ELETRÔNICA DO PROCESSO - André Fontes (TRF2, 2017)
Technological advances, as it is of general knowledge, take to be fully incorporated by the judiciary, in the light of systematic resistance and anachronistic, which can be found, with rare exceptions, in the organ that integrates it throughout the country. These apparatus cause natural initial strangeness, but in fact do not cause any injury; On the contrary, they collaborate for the speed and effectiveness of the provision of judicial protection. That is why, nowadays, the courts do not annul any more decisions and procedural acts elaborated in the typed form, through the use of microcomputers or even using laser printers. In this context, the purpose of this work is to demonstrate the possibility of using technological resources available in judicial proceedings, as a way to promote the improvement and effectiveness of judicial activities. The developing cyber-resources, as they will be exposed, can complement the exercise of jurisdiction through the use of Artificial intelligence.